The Impact Of Drug Abuse On Social And Family Economics In The Perspective Of Sharia Economics (Case Study At The Baitu Syifa Drug Rehabilitation Institution In Medan) - Jamilah Harahap; Zulkarnain Nasution; Marliyah Marliyah (UNIVED Press, 2024)
This study aims to determine the impact of drug abuse on social and family economics. To find out the impact of drug abuse on social and family economics in the perspective of sharia economics. The approach in this research is qualitative research. The subjects in this study are drug users and one of the family members of users and also members of the management of the Baitu Syifa Medan Drug Rehabilitation Institute. The data source of this research is an interview conducted to the head of the household or family members who use drugs. The data collection techniques are observation method, interview method, documentation method, triangulation. Data analysis is an effort to find and organize systematically the records of observation, interviews, by means of data reduction, data display (presentation of data), data conclusion and data verification. The impact of drug abuse on social family. The results showed that the impact of drug abuse on social indicators, namely user education and user families, concluded that both informants had completed their college education before falling into using drugs. Or it can be interpreted that they used drugs when they were already in the work environment. From a psychological point of view, this can be seen from the divorce that occurred, while the psychological impact on parents and other families is to feel depressed and frightened due to changes in the behavior of users who are very aggressive and temperamental. The impact of drug abuse on the family economy is that the three informants interviewed are all unproductive and can no longer work properly, especially since all informants have been using drugs for a very long time. HI only works twice a week, AM can no longer work. Informant S, because he owns a dental clinic business inherited from his family, can still be said to be able to work but because he is dependent on consuming 4 times a week, S also has a history of heart disease due to consuming drugs so that it will interfere with his work productivity. In the perspective of Islamic economics, every family must ensure the welfare of its family members by fulfilling their every need both in terms of social, economic, and spiritual aspects. However, a person's involvement in drug abuse will damage their economic security so that they cannot provide welfare to their family members. Users will spend their income to buy drugs so that they cannot fulfill their personal needs, borrow money from parents and relatives, and even have to pawn some of their property because they are very dependent.